ERC- roof: Low cost green roofing - Ku Izzat Iqhbal, Ku Ismail; Nurul Syafiqah Aqilah, Hasnizam (Ministry of Education, Thailand, 2012)
Ku Izzat Iqhbal Ku Ismail and his team won gold medal at 8th International Exhibition for Young Inventors (IEYI 2012), 28th - 30th June 2012 was held at Bangkok International Trade and Exhibition Centre (BITEC), Bangkok, Thailand.